Case Report: A case of cutaneous polyarteritis nodosa in a child following a streptococcal infection - Wei Cheng; Wei Yin; Fan Liu; Wen Yin (Frontiers in Pediatrics)
BackgroundPolyarteritis nodosa is a rare systemic necrotizing vasculitis that is often overlooked and misdiagnosed in clinical practice. Patients may exhibit fever, rash, myalgia, and further symptoms; in severe instances, this may result in damage to the kidney, heart, and other important organs, and may even be life-threatening. Consequently, prompt diagnosis and intervention might mitigate the occurrence of complications and improve patient prognosis.Patient presentationAn 11-year-old girl was admitted to our hospital with multi-joint pain for 7 days, accompanied by worsening fever for 4 days. The physical examination on admission revealed alterations in the skin texture characterized by scaling, a bluish-purple rash, and sensitive subcutaneous nodules on the extremities with limited mobility. Following admission, laboratory testing revealed high serum inflammatory markers, and positive anti-chain “O,” rheumatic fever was initially considered. The symptoms were not relieved after the use of antibiotics and aspirin. After reviewing the literature, polyarteritis nodosa was highly suspected, and a skin biopsy indicated necrotizing vasculitis, therefore confirming polyarteritis nodosa. The child's symptoms were alleviated with the use of glucocorticoids in conjunction with immunosuppressive medication.ConclusionThis case involves a child diagnosed with nodular polyarteritis subsequent to a streptococcal infection. For patients with a strong suspicion of polyarteritis nodosa, a timely skin biopsy or arterial angiography should be conducted to confirm the diagnosis and increase survival rates.